Efficacy and safety of tofacitinib following inadequate response to conventional synthetic or biological disease-modifying antirheumatic drugs. Issue 7 (14th August 2015) - Charles-Schoeman, Christina; Burmester, Gerd; Nash, Peter; Zerbini, Cristiano A F; Soma, Koshika; Kwok, Kenneth; Hendrikx, Thijs; Bananis, Eustratios; Fleischmann, Roy
Abstract : Objectives: Biological disease-modifying antirheumatic drugs (bDMARDs) have shown diminished clinical response following an inadequate response (IR) to ≥1 previous bDMARD. Here, tofacitinib was compared with placebo in patients with an IR to conventional synthetic DMARDs (csDMARDs; bDMARD-naive) and in patients with an IR to bDMARDs (bDMARD-IR). Methods: Data were taken from phase II and phase III studies of tofacitinib in patients with rheumatoid arthritis (RA). Patients received tofacitinib 5 or 10 mg twice daily, or placebo, as monotherapy or with background methotrexate or other csDMARDs. Efficacy endpoints and incidence rates of adverse events (AEs) of special interest were assessed. Results: 2812 bDMARD-naive and 705 bDMARD-IR patients were analysed. Baseline demographics and disease characteristics were generally similar between treatment groups within subpopulations. Across subpopulations, improvements in efficacy parameters at month 3 were generally significantly greater for both tofacitinib doses versus placebo. Clinical response was numerically greater with bDMARD-naive versus bDMARD-IR patients (overlapping 95% CIs). Rates of safety events of special interest were generally similar between tofacitinib doses and subpopulations; however, patients receiving glucocorticoids had more serious AEs, discontinuations due to AEs, serious infection events and herpes zoster. Numerically greater clinical responses and incidence rates of AEs of special interest were generally reported for tofacitinib 10 mg twice daily versus tofacitinib 5 mg twice daily (overlapping 95% CIs). Conclusions: Tofacitinib demonstrated efficacy in both bDMARD-naive and bDMARD-IR patients with RA. Clinical response to tofacitinib was generally numerically greater in bDMARD-naive than bDMARD-IR patients. The safety profile appeared similar between subpopulations. Trial registration numbers: (NCT00413660, NCT0050446, NCT00603512, NCT00687193, NCT00960440, NCT00847613, NCT00814307, NCT00856544, NCT00853385 ).